Habitual Subjective Well-Being and Movement Activity of Female Adolescents - Jaroslav Broďáni; Ľuboslav Šiška (Jan Długosz University in Częstochowa, 2019)
Purpose: This paper presents the results of a comparative and dependency analysis between physical activity, joy of physical activity and quality of life in female high school students with different levels of sport performance. Methods: The survey was attended by (n = 560) 16-19 years old high-school students. The quality of life was monitored using the modified SQUALA questionnaire, the joy of physical activity using the PACES questionnaire and the level of physical activity during the week in hours (PA). The data are presented by means of descriptive characteristics (n, M, SD) and statistical significance and dependencies respectively are assessed using nonparametric methods (W, U, rs) on significance levels (p < ,10; p < ,05 and p < ,01). Results: The results of the dependency analysis did not show a large number of interactions between the PA, PACES and SQUALA among high-school female students. We found the interactions between the PA and PACES or SQUALA sporadically in groups of girls with the different levels of sports, where positive interactions predominated. PA in the week is positively correlated with PACES (rs = ,218, p < ,10) only in registered female athletes. Positive interactions between PACES and SQUALA can be found in top female athletes (material well-being p < ,10; education p < ,05; free time p < ,01) and in occasional female athletes (physical well-being p < ,20; psychosocial well-being p < ,20; appearance and ownership of things p < ,20). Conclusions: The results confirm the importance of voluntary and organized physical activity in the life of high-school students, who have the potential to increase the level of satisfaction with activity.